Influence des composés inhibiteurs ou promoteurs dans le traitement d'un produit pharmaceutique et d'un colorant par un POA -procédé Fenton- - SLAMANI SAMIRA (My University, 2011)
This study concerns the application of various advanced oxidation processes, AOP (Fenton, photo-Fenton and solar-Fenton, photo-FentonLike and solar-Fenton Like) to treatment of wastewater containing the persistent organic pollutants such as textile dyes. The characteristic of these processes is due to the generation of very reactive and very oxidizing species, hydroxyl radicals •OH which are able to oxidize any organic molecule until the ultimate oxidation stage, i.e. mineralization (transformation into CO2 and H2O). This study examines the application of different advanced oxidation processes, AOPs for the treatment of a dye, Rhodamine B and a pharmaceutical substance, the Ampicilline. Fenton process was applied for the oxidation of dye, and ampicilline after optimization of the reagents, hydrogen peroxide and ferrous ions. The optimum ratio is respectively 3 and 11, for Rhodamine B and Ampicilline. Oxidation rates are effective from 47.01 and 52.14% for the Fenton process, 47.8 and 56.41 for the photo Fenton process and 53.85 and 58.12% for solar Fenton in a time t equal to 15 and 60 minutes for the case of dye. While for the pharmaceutical substance, oxidation rates are 50 and 58.06% for Fenton, 53.23 and 67.74% for photo-Fenton 58.06 and 62.92% for Solar-Fenton. Treatment of dye was studied in the presence of scavenger, when the degradation decreases with increasing concentration of urea or tert-butanol. The same happened to Ampicilline. Treatment of 60 min led to a rate of oxidation of 52.14%, 49.47% and 43.96% for single RhB, RhB in the presence of urea (2.395 g / l) and RhB with the Urea (23.95 g / l) respectively. The oxidation rate reached 52.14%, 33.33% and 27.59% for Rh B alone, RhB with Tert-B (0.005 M) and RhB with Tert-B (0.05 M) respectively. In the case of ampicilline, the treatment gives an inhibition of the oxidation of 58.06%, 42.03%, 28% for single Amp, Amp with urea (0.6988 g / l) and Amp in the presence Urea (1.3976 g / l) respectively. Oxidation rate of 58.06%, 23.64% and 17.24% is obtained for single Amp, Amp with tert-butanol (0.002 M) and Amp in the presence of tert-butanol (0.004 million) respectively. The concentrations of oxalic acid promoter optimal are different for the dye and the pharmaceutical substance. This concentration is 0.2395 g / l for the dye, resulting in oxidation rate of 68.04% and 80.41% for the photo Fenton and 70.91%, 79.38% for solar Fenton in 15 and 60 min. While for Ampicillin, oxalic acid is much lower than previously, with a concentration of 0, 0.028 g / l to oxidation is optimal, we obtained 89.74% and 79.49% for Fenton and photo-Fenton, 82.05% and 92.31% for solar Fenton in 15 and 60 min. A comparative study for the oxidation of these substances was examined by using ferric ions instead of ferrous ions in the photochemical treatment, the results are similar. In conclusion, we can say that the Fenton process is a promising treatment and oxalic acid is an effective promoter improves significantly the degradation of organic pollutants that it is in the presence of artificial UV or natural light.
Keywords: Advanced OxidationProcess, Fenton, photo-Fenton, solaire-Fenton, Fenton Like, scavenger, promoter, decolorization, degradation, Hydroxylradicals, dye, Ampicilline.